Multi-wall carbon Nanotube surface-based functional nanoparticles for stimuli-responsive dual pharmaceutical compound delivery - Masoumeh Nabitabar; Maryam Shaterian; Hossein Danafar; Morteza Enhessari (Scientific Reports)
Abstract Carbon nanotubes (CNTs) have the potential to serve as delivery systems for medicinal substances and gene treatments, particularly in cancer treatment. Co-delivery of curcumin (CUR) and Methotrexate (MTX) has shown promise in cancer treatment, as it uses fewer drugs and has fewer side effects. This study used MTX-conjugated albumin (BSA)-based nanoparticles (BSA-MTX) to enhance and assess the efficiency of CUR. In-vitro cytotoxicity tests, DLS, TEM, FTIR, UV/Vis, SEM, and DSC studies assessed the formulations' physical and chemical properties. The Proteinase K enzyme was used to severe amidic linkages between MTX and BSA. The findings demonstrated the efficacy of using ƒ-MWCNT-CUR-BSA-MTX as a vehicle for efficient co-delivery of CUR and MTX in cancer treatment. The MTT colorimetric method was used to evaluate the effect of chemical and medicinal compounds. Cell division was studied using the MTT method to investigate the effect of pure MWCNT, pure CUR, MTX-BSA, and ƒ-MWCNT-CUR-MTX-BSA. Studies on cell lines have shown that the combination of curcumin and MTX with CNT can increase and improve the effectiveness of both drugs against cancer. A combination of drugs curcumin and methotrexate simultaneously had a synergistic effect on MCF-7 cells, which indicated that these drugs could potentially be used as a strategy for both prevention and treatment of breast cancer. Also, ƒ-MWCNT-CUR-MTX-BSA was found to have a significant effect on cancer treatment with minimal toxicity compared to pure curcumin, pure MTX-BSA, MTX, and ƒ-MWCNT alone. Unique properties such as a high ratio of specific surface area to volume, high chemical stability, chemical adsorption ability, high capacity of drug and biomolecules of carbon nanotubes, as well as multiple drug loading at the same time The combination of ƒ-MWCNT-CUR-BSA MTX significantly impacts cancer therapy), are desirable as an alternative option for targeted drug delivery and high therapeutic efficiency.